A 15 Year Ecological Comparison for the Market Dynamics of Minnesota Community Pharmacies from 2002 to 2017 - Anthony W. Olson; Jon C. Schommer; Ronald S. Hadsall (MDPI AG, 2018)
Background: Understanding the factors that influence the market entry, exit, and stability of community pharmacies (i.e., market dynamics) is important for stakeholders ranging from patients to health policymakers and small business owners to large corporate institutions. Objective: The study’s first objective was to describe the market dynamics of community pharmacies for Minnesota counties in 2002, 2007, 2012, and 2017 by associating county (a) population density and (b) metropolitan designation with the change in the number of ‘All community pharmacies,’ ‘Chain community pharmacies’, and ‘Independent community pharmacies’. The study’s second objective was to describe the number and proportion of community pharmacies for Minnesota counties in 2002, 2007, 2012, and 2017 by (1) ‘Business Organization Structure’ and (2) ‘Pharmacy Type.’ Methods: County-level data were obtained from the Minnesota Board of Pharmacy, US Census Bureau, and Minnesota State Demographic Center for 2002, 2007, 2012, and 2017. Findings were summarized and the associations between study variables described using descriptive statistics. Results: The ratio of ‘Independent community pharmacies’ to ‘Chain community pharmacies’ was about 1:1 (466:530) in 2002, 1:2 (352:718) in 2007, 1:2 (387:707) in 2012, and 1:3 (256:807) in 2017. There was not a consistent relationship that carried through the 15 year analysis between county population density and metropolitan designation and the market dynamic patterns of community pharmacies. The types of pharmacy in Minnesota changed significantly over the study with increases in state, regional, and national chains and declines in single entity and small chain independents. There were also notable declines in mass merchandiser community pharmacies and increases in clinic and medical center community pharmacies. Discussion: The findings suggest that different or additional factors beyond traditional market dynamic predictors of population density and metropolitan designation were at play in each five year interval of this study. We propose that the traditional dichotomy of independent and chain community pharmacy groupings no longer provide an optimal characterization for the market dynamics of pharmacies today. Instead, community pharmacies may be better organized by their capacity to operate as healthcare access points that provide and are reimbursed for patient care and public health services like medication therapy management, immunizations, and more. Conclusions: The findings showed that community pharmacy distribution in Minnesota’s 87 counties has shifted between 2002 and 2017 from traditional retail models to emerging healthcare models based on population health needs. This signals the need for not only a new approach for tracking community pharmacy market dynamics but also adjustments by community pharmacies to remain relevant in a new environment of patient care services.